PENERAPAN METODE PELATIHAN PLIOMETRIK DALAM MENINGKATKAN POWER OTOT TUNGKAI ATLET PPLM BALI - Suratmin; I Putu Panca Adi (Journal of Physical Education Health and Sport, 2016)
The purpose of this study was to assess and prove the application of plyometrics training methods to improve limb muscle power athletes PPLM Bali. This study consisted of independent variables is plyometrics training methods, while the dependent variable is the leg muscle power. The research method using a quasi-experimental methods. The sample in this study is the athletes PPLM Bali. Data obtained with the test beginning and the end namely leg muscle power. Data were analyzed using a statistical test infrensial through t-test at a significance level of 5%. The results showed that: (1) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, (p <0.008), (2) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, laboratory tests (p <0.003), (3) there is a significant improvement between the initial tests and final test against power leg muscle with a test jump upright, field tests of 8.64%, (4) there is a significant increase between tests initial and final test against power leg muscle with a test jump upright, laboratory tests for 5:04%, (5) there is a significant improvement between the initial tests and final test against power leg with a test jump without prefix / standing broad jump (p <0.000), and (6) there is a significant improvement between the initial test and final test against power leg with a diving tests without prefix / standing broad jump of 23%